PREPARING FUTURE DOCTORS FOR INNOVATIVE PROFESSIONAL ACTIVITIES - Mamajanova Erkinoy Abdurasulobna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
The rapidly evolving landscape of healthcare necessitates a paradigm shift in medical education to prepare future doctors for innovative professional activities. This article explores the essential components of contemporary medical education, focusing on the integration of advanced technologies, interdisciplinary collaboration, and adaptive learning methodologies. By examining current trends and future projections, this paper aims to provide a comprehensive overview of strategies to equip medical students with the skills and knowledge required for future challenges and opportunities in the medical field.